BEST RAW MATERIAL STORAGE METHOD FOR KEEPING QUALITY OF FOOD PRODUCTION - Vincent Audi Santoso (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Food is a basic human need that is needed at all times and requires good and proper management in order to benefit the body. According to WHO, the intended food is: “Food include all substances, whether in a natural state or in a manufactured or preparedform, wich are part of human diet.”These food restrictions do not include water, medicines and substances needed for medicinal purposes.